RYR1 gene variability and effect on meat pH in Argentinean hybrids swines - Marini, S.J. (2012)
The RYR1 gene is the principal cause of the porcine stress syndrome (PSS) and the presence of pale, soft and exudative meat (PSE) in swine. In Argentina there are no reports about the variability of RYR1 gene in hybrid swine and its effect on the quality of carcass. \nBy PCR-HRM we analyzed 403 hybrids swines from Argentina and 65.0% were homozygous NN, 30.8% heterozygous Nn and 4,2% homozygous nn. Additionally, a significant effect (p <0.0001) of the RYR1 gene was detected on the pH of carcass at 45 minutes after slaughter. Normal genotypes NN showed the highest pH values at 45 minutes after slaughter (6.27), heterozygous Nn showed intermediate pH values (5.94) and homozygous susceptible nn showed the lowest pH values (5.64). Argentina present high incidence of Nn and nn genotypes for the RYR1 gene in relation to Brazil, the principal pig producer of Latin America. Additionally the RYR1 gene affects the pH of the meat, one of the principal parameters in the determination of the PSE meat.